Deformation Parameters and Collective Temperature Changes in Photofission Mass Yields of Actinides Within the Systematic Statistical Scission Point Model - Kadiani, P. Mehdipour (Frontiers in Physics, 2021)
The photofission fragments mass yields of actinides are evaluated using systematic statistical scission point model. In this model, all energies at scission point are presented as a linear function of the mass numbers of fission fragments. The mass yields are calculated with an new approximated relative probability for each complementary fragment. The agreement with the experimental data is quite good, specially with a collective temperature T_col of 2 MeV at intermediate excitation energy and T_col = 1 MeV for spontaneous fission. This indicates that the collective temperature is greater than the value obtained by the initial excitation energy. The generalized superfluid model is applied for calculating the fragments temperature. The deformation parameters of fission fragments have been obtained by fitting the calculated results with the experimental values. This indicates that the deformation parameters decrease with increasing the excitation energy. Also, these parameters decrease for odd mass number fissioning systems.